Die Lebenszeugnisse Oswalds von Wolkenstein, Band 2 Band 2: 1420 - 1428; Nr. 93 - 177, Edition und Kommentar - Schwob, Anton (2001)
While the first volume presented a younger son of a family of Tyrolese nobility, who strived after social advancement throughout Europe and who succeeded to act the part of a special advisor in service of the sovereign, the documents of his life in the second volume concentrate primarily on feuds, captivities and resolution of conflicts in Tyrol. The conflict over the heritage of Hauenstein leads to captivity, provisional release, appeal to the king, further imprisonment and humiliating submission to the duke of Tyrol. Finally Oswald is granted a reprieve and acquires the property of Hauenstein.